2017
DOI: 10.1002/pen.24492
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the electrospinning processing‐window to fabricate nanostructured PE‐b‐PEO and hybrid PE‐b‐PEO/EBBA fibers

Abstract: An electrospinning technique is used to obtain poly(ethylene-b-ethylene oxide) block copolymer (PE-b-PEO) fibers. Optimization of the electrospinning processing-window is carried out by varying the concentration of the block copolymer solution and playing with three different electrospinning parameters, applied voltage, solvent and block copolymer solution flow rate. The influence of the concentration of the block copolymer solution over the length and diameter of the fibers is mainly studied and results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Lactic acid oligomer (Glyplast OLA8, ester content >99%, density 1.11 g•cm −3 , viscosity 22.5 mPa.s, molecular weight 1100 g•mol −1 ) was kindly supplied by Condensia Quimica SA. PLA:OLA electrospun fiber mats were prepared in an Electrospinner Y-flow 2.2.D-XXX (Nanotechnology Solutions) following our previously reported protocol [25][26][27], working conditions of 22% of humidity and a temperature of 20 • C. Briefly, the polymers are solved in a solvent solution of chloroform:dimethilformamide, in a proportion of 4:1, overnight at ambient conditions. Then, the optimization of the main parameters of the electrospinning process were achieved and a voltage of 20 V, a distance of 17 cm between tip and collector and a polymer solution flux of 3.5 mL/h were used in order to obtain randomly-oriented electrospun fiber mats.…”
Section: Methodsmentioning
confidence: 99%
“…Lactic acid oligomer (Glyplast OLA8, ester content >99%, density 1.11 g•cm −3 , viscosity 22.5 mPa.s, molecular weight 1100 g•mol −1 ) was kindly supplied by Condensia Quimica SA. PLA:OLA electrospun fiber mats were prepared in an Electrospinner Y-flow 2.2.D-XXX (Nanotechnology Solutions) following our previously reported protocol [25][26][27], working conditions of 22% of humidity and a temperature of 20 • C. Briefly, the polymers are solved in a solvent solution of chloroform:dimethilformamide, in a proportion of 4:1, overnight at ambient conditions. Then, the optimization of the main parameters of the electrospinning process were achieved and a voltage of 20 V, a distance of 17 cm between tip and collector and a polymer solution flux of 3.5 mL/h were used in order to obtain randomly-oriented electrospun fiber mats.…”
Section: Methodsmentioning
confidence: 99%
“…There are many factors affecting the formation of these undesired structures, such as solution properties (e.g., viscosity, conductivity, volatility, and surface tension) and the electrospinning parameters (e.g., feed rate, applied voltage, the distance between the collector and the tip). [71][72][73][74][75] Since electrospinning parameters were kept constant for all mats, the transformation of the beaded fiber morphology into a homogeneous morphology of smooth fibers without any beads are attributed to the changes in viscosity, conductivity, and surface tension of the spinning solutions as a result of BPPTA reinforcement. However, misalignment and folding of the nanofibers seem to increase after 3% BPPTA content due to the strong interactions between the polymer constituents.…”
Section: Morphological Analysis Of the Cnmsmentioning
confidence: 99%
“…Mathieu et al 19 demonstrated the feasibility of electrospinning protein polymer multiple scaffolds using SS/PEO electrospinning on PLA. Carrasco et al 20 used electrospinning to prepare poly(ethylene‐b‐ethylene oxide) block copolymer (PE‐b‐PEO) fibers. The process window of electrospinning was optimized by changing different parameters of electrospinning.…”
Section: Introductionmentioning
confidence: 99%